The Relationship of Leadership Styles and Organizational Culture Case Study of an Oil and Gas Company in Indonesia - Tommy K Darwis, Surna Tjahja Djajadiningrat (ITB, 2010)
This Study exploresrelationship between leadership styles and organizational culture in an oil and gas Company in Indonesia. The respondents are employes of an oil and gas company in Indonesia. This study use Multifactor leadership questionnaires to define leadership styles and Denisons's Organizational Culture Model to measure Organizational Culture. These quetionnaires were used to measure leadership styles of ommediate or direct supervisor and organizational culture of unit or division. The data were analyzed with descriptive and use correlational analysis. A relationship exixts between the leadership styles of ommediate or direct supervisor and organizational culture. In three Leadership styles of Multifactor leadership, Positive corelation was found between Trahsformational Leadership Style and Organizational Culture. Transformastional Leadership found as strong predictor of organizational Culture and conversely. Laissez-Faire Leadership style has negative correlation with organizational culture. Transformastional, Transactional Leadership and high level of organizational culture will be make good impact for maintaining and achieving excelent organizatonal performance for company.